In vitro antioxidant, antibacterial and membrane stabilizing activity of plant extract from Chrysanthemum fontanesii - Amel amrani,; Boubekri Nassima,; Benaissa Ouahiba,; Zama Djamila,; Benayache fadila,; Benayache Samir, (International Journal of Phytomedicine, 2013)
Antioxidant activities, antibacterial and membrane stabilizing activity of butanolic extract from leaves of Chrysanthemum fontanesii were investigated. The inhibition of the formation of malondialdehyde (MDA) in vitro and the scavenging of DPPH were assayed .The phenolic content of the extract was determined. The experimental results show that butanolic extract have antioxidant activity in vitro. The extracts showed a high antioxidant effect, especially scavenging of DPPH anions and inhibition of lipid peroxidation. Antioxidant activities were compared to ascorbic acid. The total content of phenolic compounds was 349 µg of gallic acid equivalents/mg extract. The butanolic extract was effective against microorganisms and against heat-as well as hypotonic solution-induced haemolysis of erytrocytes in vitro.